A case of desmoplastic myxoid tumor, SMARCB1 mutant, in the pineal region. Issue 1 (9th September 2020) - Wang, Yue‐E.; Chen, Jing‐Jing; Wang, Wei; Zhang, An‐Li; Zhou, Wenchao; Wu, Hai‐Bo
Abstract : Desmoplastic myxoid tumor (DMT), SMARCB1 mutant is a recently proposed new entity that mainly occurs in the pineal region and has epigenetic features similar to those of atypical teratoid/rhabdoid tumors (AT/RT)‐MYC and poorly differentiated chordomas. Herein, we present a new case of a 33‐year‐old man with headaches, dizziness, nausea, vomiting, and blurred vision, who was initially found to have a suspicious germinoma on imaging. After surgical removal of the lesion, the postoperative pathological diagnosis was DMT, SMARCB1 mutant. To the best of our knowledge, this is the first case reported in China. Our findings also extend the range of the immunohistochemical phenotype of this rare tumor.